XANES measurements probing the local order and electronic structure of Pb1-xBaxZr0.40Ti0.60O3 ferroelectric materials - Mesquita, A. [UNESP]; Michalowicz, A.; Mastelaro, V. R. (Elsevier B.V., 2015)
In this study, the electronic and local structures of Pb1-xBaxZr0.40Ti0.60O3 ferroelectric ceramic samples were characterized using X-ray absorption near-edge structure (XANES) measurements. The analysis of XANES spectra collected at the Ti K-and L-edges showed that the substitution of Pb by Ba leads to a decrease in the local distortion around the Ti atoms in the TiO6 octahedron. The analysis of O K-edge XANES spectra and density of states ab initio calculations showed that the hybridization between the O 2p and Pb 6sp states is related to the displacement of Ti atoms in the TiO6 octahedra. Based on these results, it is possible to determine that the degree of ferroelectricity in these samples and the manifestation of relaxor behavior are directly related to the weakening of O 2p and Pb 6sp hybridization. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Ferroelectrics; Relaxor; X-ray absorption; Perovskite; Lead zirconate titanate; PBZT